A child with a foreign body in bronchus misdiagnosed as asthma. Issue 12 (21st July 2020) - Chaudhary, Nagendra; Shrestha, Sandeep; Kurmi, Om P.
Abstract: Foreign body ingestion should be considered as an important differential in a child with difficult asthma. We report an 11‐year‐old male child with foreign body aspiration who initially was diagnosed and treated as difficult asthma. Later on, he was diagnosed to have a foreign body in the right bronchus, which was successfully removed by flexible bronchoscopy. Abstract : Foreign body ingestion should be considered as an important differential in a child with difficult asthma. We report an 11‐year‐old male child with foreign body aspiration who initially was diagnosed and treated as difficult asthma. Later on, he was diagnosed to have a foreign body in the right bronchus, which was successfully removed by flexible bronchoscopy.